Bi-fidelity surrogate modeling with Subset Simulation for structural reliability assessment - Lima, João Paulo Silva (2023)
Tese (doutorado) — Universidade de Brasília, Programa de Pós-Graduação em Estruturas e Construção Civil, Faculdade de Tecnologia, 2023.